Membrane-bound geranylgeranyl diphosphate phosphatases: Purification and characterization from Croton stellatopilosus leaves - Nualkaew, N.; De-Eknamkul, W.; Kutchan, T.M.; Zenk, M.H.
Geranylgeranyl diphosphate phosphatase is an enzyme catalyzing the dephosphorylation of geranylgeranyl diphosphate (GGPP)to form geranylgeraniol (GGOH). The enzyme activity of GGPP phosphatase was detected in leaves of Croton stellatopilosus, a Thai medicinal plant containing plaunotol, a commercial anti-peptic acyclic diterpenoid. Enzymological studies of GGPP phosphatase in C. stellatopilosis leaves revealed that the enzyme is a membrane-bound protein that could be removed from 20,000g pellet by 0.1
Keywords: CROTON STELLATOPILOSUS; EUPHORBIACEAE; GERANYLGERANIOL; GERANYLGERANYL DIPHOSPHATE; GERANYLGERANYL DIPHOSPHATE PHOSPHATASE; ACYCLIC DITERPENE BIOSYNTHESIS; ENZYME PURIFICATION; ENZYME CHARACTERIZATION